Applying 3D scanning and CAD reverse engineering for clothing thermal analysis. Issue 1 (1st January 2021) - Špelić, Ivana
Abstract: Combining 3D scanning and CAD reverse engineering is currently the only possible method to acquire the precise geometric calculation of clothed human body. To obtain realistic geometric CAD human body models, computer-assisted sequential reverse engineering was performed. The male modular jacket and corresponding whole-body clothing ensembles were afterwards tested by static thermal manikin. By combining precise thermal properties of clothing in respect to established geometrical features of each dressed CAD human body model, correlation has been ascertained between geometry and thermal insulation properties of clothing. The study has proven that the length of the outerwear items such as jackets, significantly impacts the changes in area and volume and substantially leads to increase in the thermal insulation value of the whole-body clothing ensembles. A 20 cm jacket's length enlargement leads to as much as 10.4% area increase and 22.0% volume increase in overall clothing ensemble and accounts for more than 25% increase in effective thermal insulation. The maximum jacket's length increase for 60 cm led to ensemble's area increase of 26.5% and volume increase of 75.5%. As observed, the increase in length for 60 cm simultaneously led to substantial increased in both overall volume and area and accounted for effective insulation increase for as much as 41.7%. The study has proven the causal link between the garment's length and consequential changes to geometrical clothing features, which directly affect the potential decrease or increase in the effective thermal insulation value. Graphical abstract: